2014
DOI: 10.1016/j.intimp.2014.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of recombinant lactoferrin during MRSA infection

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) infection remains a serious hazard to global health despite increases in public education and development of innovative treatment strategies. Use of immune modulatory therapy to combat infection is gaining interest as a novel treatment alternative. Lactoferrin (LF), an iron binding protein with multiple immune modulating properties, has the potential to modify the course of systemic MRSA infection. Specifically, LF is capable of limiting deleterious inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 52 publications
0
18
0
1
Order By: Relevance
“…LF has the potential to modify the course of an infection [42]. Being immunomodulator, LF is used as adjunct therapeutic which can alter the immune status of the infected host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LF has the potential to modify the course of an infection [42]. Being immunomodulator, LF is used as adjunct therapeutic which can alter the immune status of the infected host.…”
Section: Discussionmentioning
confidence: 99%
“…But the two heterologous recombinant molecules showed some differences in their activities concerning cellular population that were used in the studies-mouse granulocytes demonstrated a different cytokine pattern upon the infection than human granulocytes. LFs were produced under endotoxin free serum conditions, and further affinity purified to remove traces of endotoxin [42]. The data show that endotoxin-free LF has not only immunomodulatory effects but also the therapeutic effects which have different essence than just LPS binding.…”
Section: Discussionmentioning
confidence: 99%
“…Proper inflammatory response is essential to eradicate infectious microorganisms [35]. However, excessive inflammation could cause damage to the body with a large number of activated immune cells and the excessive release of inflammatory factors [36,37]. At three days after treatment, amphenmulin could significantly decreased TNF-α, IL-6, and MCP-1 in the serum in comparison to those of the infection group, avoiding the adverse effects of excessive inflammatory factors on wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Activated Mø express and release lactoferrin, which scavenges and restricts Fe availability to extracellular pathogens (Fig ). Lactoferrin also protects Mø from oxidative stress and modulates Mø microbicidal activity, as shown in the context of Staphylococcus aureus infection . The Fe‐binding capacity of lactoferrin can also interfere with microbial virulence pathways such as biofilm formation .…”
Section: Regulation Of Fe Metabolism As a Host Resistance Mechanism Amentioning
confidence: 99%